2019
DOI: 10.1111/liv.14037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of inflammatory response in hepatorenal syndrome: Relationship with kidney outcome and survival

Abstract: Background Several lines of evidence indicate that decompensated cirrhosis is characterized by the presence of systemic inflammation. Hepatorenal syndrome (HRS‐AKI) is a unique type of renal failure that occurs at late stages of cirrhosis. However, confirmation of the presence and significance of such inflammatory response in HRS‐AKI is lacking. Aim and Methods To characterize the systemic inflammatory response, as estimated by measuring a large number of cytokines, in 161 patients hospitalized for an acute de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 25 publications
2
52
0
3
Order By: Relevance
“…Previous studies demonstrated an association between high circulatory inflammatory markers, eg, CRP, 18,19 and inflammatory cytokines at baseline 12,20,21 and increased mortality in AD/ACLF. In our cohort baseline clinical characteristics of the survivors and nonsurvivors were quite similar aside from serum creatinine and a non-significant increase in MELD score and infection rate, which may be due to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated an association between high circulatory inflammatory markers, eg, CRP, 18,19 and inflammatory cytokines at baseline 12,20,21 and increased mortality in AD/ACLF. In our cohort baseline clinical characteristics of the survivors and nonsurvivors were quite similar aside from serum creatinine and a non-significant increase in MELD score and infection rate, which may be due to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 94%
“…28 More over, plasma concentrations of proinflammatory injury; CKD=chronic kidney disease; NAKI=non-acute kidney injury; NSAID=non-steroidal anti-inflammatory drug; RBC=red blood cell doi: 10.1136/bmj.m2687 | BMJ 2020;370:m2687 | the bmj cytokines (interleukin6, tumor necrosis factorα (TNFα), vascular cell adhesion protein1, and interleukin8) and urinary concentrations of mono cyte chemoattractant protein1 are increased in patients with AKIHRS compared with those with decompensated cirrhosis without AKI and patients with AKI secondary to prerenal azotemia. 29 Inflammation in cirrhosis is driven by two groups of molecules: pathogen associated molecular patterns (PAMPs) and damage associated molecular patterns (DAMPs). PAMPs represent bacterial products, such as lipopolysaccharide, flagellin, and nigericin, which result from translocation of gut bacteria or bacterial infections, whereas DAMPs represent intracellular components released from injured hepatocytes, including high mobility group protein B1, heat shock protein, adenosine triphosphate, double stranded genomic DNA, and others.…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Downloaded from treatment, including model for end stage liver disease (MELD) score, 126 pretreatment serum creatinine concentration, 22 23 sepsis, 126 extrahepatic organ failure, 127 and systemic inflammation. 29 Lower serum creatinine concentrations at the start of treatment are associated with higher rates of HRS reversal, whereas only a negligible response is expected when creatinine exceeds 7 g/dL. 22 23 Thus, earlier diagnosis of AKIHRS with the elimination of creatinine concentration cutoff, will likely result in higher rates of response to treatment.…”
Section: Side Effectsmentioning
confidence: 99%
“…Останнім часом стає все більш очевидним, що цироз печінки є станом із вираженою системною запальною відповіддю (ССЗВ), яка збільшується із прогресуванням хвороби, від компенсованого до декомпенсованого цирозу, і сильно впливає на прогноз пацієнта [9]. У деяких клінічних дослідженнях оцінювали запалення при цирозі шляхом вимірювання кількості лейкоцитів або рівнів С-реактивного білка (CРБ) [10,11]; однак ці методи не є досить точними для оцінки запалення. Окрім того, дослідження на експериментальних тваринах також продемонстрували наявність ССЗВ, яка є більш помітною у тварин із асцитом, порівняно з іншими [12].…”
Section: вступunclassified